CompTIA cybersecurity analyst (CSA+). - Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The CompTIA Cybersecurity Analyst, or CSA+, is a CompTIA certification focusing on the knowledge and skills required to configure and use threat-detection tools, perform data analysis, and interpreting the results with the end goal of securing an organization's applications and systems. The CSA+ is a vendor neutral certification that expects three to four years of experience in a related field as well as a Security+ or equivalent knowledge. In this regard, the CSA+ lies between the security+ as well as the CompTIA Advanced Security Practitioner (CASP) exams and is an excellent go between to tackle before diving into the CASP, but when the Security+ isn't enough. With the ongoing requirement for government agencies to receive certifications, the CSA+ was developed with a focus on meeting government requirements to certify IT workers or contractors. This certification will display an understanding of security best practices and protocols beyond that which is provided by the Security+ and will prove a level of expertise beyond that of basic security practices that are followed when using a computer. This allows any employee to prove a better understanding of enterprise security practices, and the necessary tools needed to protect a company network. The modules of this course align with the official objects of the certification and will expand past the scope of the certification to provide real life examples as well as lead ins to direct further study. This will give students more to work off of than simple definition based review and allow for easier understanding of the material for the certification as well as a basic understanding for real life application. "--Resource description page.
Title from resource description page (Safari, viewed January 18, 2018).
Keywords: Computing Technology Industry Association -- Examinations -- Study guides; Computer security -- Examinations -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books